2019
DOI: 10.1186/s13287-019-1441-4
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule destabilization caused by silicate via HDAC6 activation contributes to autophagic dysfunction in bone mesenchymal stem cells

Abstract: BackgroundSilicon-modified biomaterials have been extensively studied in bone tissue engineering. In recent years, the toxicity of silicon-doped biomaterials has gradually attracted attention but requires further elucidation. This study was designed to explore whether high-dose silicate can induce a cytotoxicity effect in bone mesenchymal stem cells (BMSCs) and the role of autophagy in its cytotoxicity and mechanism.MethodsMorphologic changes and cell viability of BMSCs were detected after different doses of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Autophagolysosomes degrade the contents to achieve cell homeostasis and organelle renewal ( 31 ). HDAC6 is involved in the regulation of autophagy at multiple levels, including participation in post-translational modifications (PTM) of autophagy-related transcription factors ( 32 , 33 ), the formation of aggresomes that are routinely cleaned through the autophagy pathway ( 22 , 34 , 35 ), and the transportation and degradation of autophagosomes ( Figure 1 ) ( 23 , 25 ).…”
Section: The Role Of Hdac6 In Autophagymentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagolysosomes degrade the contents to achieve cell homeostasis and organelle renewal ( 31 ). HDAC6 is involved in the regulation of autophagy at multiple levels, including participation in post-translational modifications (PTM) of autophagy-related transcription factors ( 32 , 33 ), the formation of aggresomes that are routinely cleaned through the autophagy pathway ( 22 , 34 , 35 ), and the transportation and degradation of autophagosomes ( Figure 1 ) ( 23 , 25 ).…”
Section: The Role Of Hdac6 In Autophagymentioning
confidence: 99%
“…Furthermore, Li et at. found that HDAC6 inhibited the transportation of autophagosomes to fuse with lysosomes through the deacetylation of α-tubulin, resulting in the depolymerization of microtubules ( 25 ). In conclusion, HDAC6 suppresses the formation and degradation of autophagosome via deacetylation the microtubules.…”
Section: The Role Of Hdac6 In Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested HDAC6 inhibition would block the fusion stage of autophagosome and lysosome, then lead to decreased autophagy activity. However Zheng et al (2020b) found that HDAC6 inhibition restored autophagy flux in axonal regeneration and Li et al (2019) found HDAC6 inhibition induced autophagy flux in BMSCs. As HDAC6 regulates autophagy at multiple levels, it influences autophagy differently due to the cell type and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HDAC6 has a function in bone diseases. Li et al ( 24 ) revealed that HDAC6 activity was increased following high-dose silicate treatment, and HDAC6 inhibition could protect bone mesenchymal stem cells by improving the microtubule structure and autophagic activity. Wang et al ( 25 ) indicated that HDAC6 knockdown promoted ALP activity and mineralized nodule formation in dental mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%